Analysis of The Effect of Information and Communication Technology on the Production of Micro and Small Enterprises in Indonesia - Taufik Heryasa; Atik Purmiyati (MediaTrend, 2022)
At present, the Indonesian business world is still dominated by Micro and Small Enterprises (MSE). From the results of the 2016-Advanced Economic Census, the number of these businesses reached more than 26 million businesses or 98.68 percent of the total non-agricultural businesses in Indonesia. This business is also able to absorb more than 59 million workers or around 75.33 percent of the total non-agricultural workforce. The advantages of MSEs include generally producing consumer goods and services that are close to the needs of the community, not relying on imported raw materials and more utilizing local resources both in terms of human resources, capital, raw materials, and equipment, and using their own capital or not supported by loans. from the bank. On the other hand, the limitations of MSEs include the lack of access to banking, the ability and knowledge of human resources that are still low so that they are managed in a simple way, the use of limited technology, and has not been able to keep up with changing consumer tastes, especially those that are export-oriented. The rapid development of information and communication technology has an impact on changes in lifestyle, including consumption patterns and the way people sell and shop. The phenomenon of e-commerce provides an easy way to shop for people by not having to come directly to the store. This can be used by MSEs to reach larger consumers so as to increase their production and income. This study aims to analyze the effect of Information and Communication Technology on the production of Micro and Small Enterprises in Indonesia. This study uses panel data from 34 provinces in Indonesia between 2015-2020 which is estimated using the Generalized Method of Moments (GMM). The results show that capital, labor, computer users, fixed wireline users, cellular phone users, internet users and telecommunications expenses simultaneously have a positive and significant impact on the production of Micro and Small Enterprises in Indonesia. Partially, capital has a positive and significant effect on the production of Micro and Small Enterprises in Indonesia. On the other hand, telecommunications spending has a negative and insignificant effect on the production of Micro and Small Enterprises in Indonesia. While other variables have a positive and insignificant effect on economic growth in Indonesia. With these results, it is hoped that the government will issue policies to support micro and small businesses in increasing the use of information and communication technology to increase their production. Among other things, by building telecommunications infrastructure in areas that are not yet adequate, providing education to micro and small business actors in using information and communication technology, and providing light credit in the form of smartphones and computers to micro and small businesses so that they can be used to promote their products on the internet.